2006
DOI: 10.1097/01.pdm.0000213469.85301.d6
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Distribution of Immunoglobulin VH Gene Usage in a Cohort of B-CLL Patients From a Northeastern Region of Italy

Abstract: We analyzed individual VH gene rearrangements in 55 consecutive B-chronic lymphocytic leukemia (B-CLL) patients collected from a northeastern region of Italy, stressing the possible differences related to geographic characteristics of the cohorts studied. Considering the percentage of somatic mutations present in the VH gene sequences and using the 98% cut-off value, 38 of the 55 B-CLL (69%) patients displayed somatic hypermutations and 17 (31%) had a germline configuration. Our results confirm and extend the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 41 publications
8
17
0
2
Order By: Relevance
“…IGHV4 family has been reported to be overused in the mutated subgroup of CLL [26]. In keeping with these findings, we confirmed the significantly preferential use of IGHV4 family in M-CLL ( P = 0.02) and the consequently better outcome of this subgroup with a longer TTFT ( P = 0.001).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…IGHV4 family has been reported to be overused in the mutated subgroup of CLL [26]. In keeping with these findings, we confirmed the significantly preferential use of IGHV4 family in M-CLL ( P = 0.02) and the consequently better outcome of this subgroup with a longer TTFT ( P = 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…IGHV gene usage family distribution was also comparable to those observed in Western countries [26], which showed a higher representation of the IGHV3 family followed by IGHV1 and IGHV4 (48.4%, 24.9%, and 18.6%, resp. ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…36,37 Similar to Mediterranean countries, we encountered the V H 3-23 family much more frequently than V H 3-21, the prevailing family in Scandinavian countries, which we observed in one single patient. 38,39 The constant presence of CD27 found in both mutated and non-mutated small lymphocytic lymphomas supports the view that small lymphocytic lymphoma cells derive from memory B cells. 40,41 Although the memory cell origin of mutated small lymphocytic lymphoma that has transited the GC is feasible, the same origin is difficult to understand for the non-mutated small lymphocytic lymphoma.…”
Section: Discussionsupporting
confidence: 55%
“…IGHV 3-21 which is commonly used in persons of predominately European descent with CLL is rarely used in Asians with CLL [14,17,37,[41][42][43][44]. In Asians and persons of predominately European descent with CLL IGHV 4-34, IGHV 3-07, IGHV 3-23 and IGHV 3-30 are commonly rearranged [14,17,36,37,40,41,45]. Recently, a direct comparison reported that V1-69 and V1-02 were under-represented in Chinese with CLL whereas V4-59, V3-07 and V4-39 were over-represented compared with Italians with CLL [38].…”
Section: Ighv Mutations and Repertoirementioning
confidence: 98%